PHENYTOIN-INDUCED ACUTE GENERALIZED EXANTHEMATOUS PUSTULOSIS - Patil, Navin; Kunder, Sushil Kiran; A, Avinash; Pathak, Anurag; Madhyastha, Sharath; Rao N, Karthik; Rao, Raghavendra (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Phenytoin is the first line antiepileptic for generalized tonic-clonic seizures. It is still the go toâ€ drug despite the availability of newer antiepileptics, chiefly because of its low cost and high efficacy. Phenytoin is associated with toxicities involving multiple organ systems such as brain, blood, and skin. One of the most common adverse effects is the development of skin rashes. It can range from mild to life-threatening skin eruptions. This is a case report of a young girl who developed acute generalized exanthematous pustulosis following phenytoin therapy for posttraumatic seizures. Keywords: Drug-induced rash, Anti-epileptic, Type-4 hypersensitivity, Hydantoin